Reflective Practice in Social Work - Knott, Christine; Scragg, Terry (Los Angeles : Learning Matters, 2016)
Reflective practice is a key learning and development process on social work courses. This title looks at the concept of reflection and reflective social work practice from a critical stance, and in accessible ways involving case material and practical tasks.
Previous edition: 2013.
Includes bibliographical references and index.
Keywords: Social service -- Philosophy; Reflection (Philosophy); Social service -- Practice; Social service -- Psychological aspects; Society